Terahertz virus-sized gold nanogap sensor - Ji, Gangseon; Kim, Hwan Sik; Cha, Seong Ho; Lee, Hyoung Taek; Kim, Hye Ju; Lee, Sang Woon; Ahn, Kwang Jun; Kim, Kyoung Ho; Ahn, Yeong Hwan; Park, Hyeong Ryeol (Nanophotonics, 2023)
We demonstrated an ultra-sensitive terahertz virus detection method combined with virus-sized gold nanogaps filled with Al2O3. Large-area high-density 20 nm-gap rectangular loop structures, containing a resonant frequency in the terahertz range, were fabricated on a 4-inch wafer using atomic layer lithography. When target viruses with a 60 nm diameter were located on the nanogaps, we observed a significant redshift of the resonant peak already with an average number of about 100 viruses per unit loop due to the strong field confinement and enhancement near the gap. Furthermore, when the virus was tightly attached to an etched gap like a bridge connecting metals, its sensitivity is doubled compared to the unetched gap, which resulted in 400% more resonance frequency shift per single virus particle than our previous work. Full-wave simulations and theoretical calculations based on modal expansions were in good agreement with the experiments, revealing that the resonant transmission spectrum was mostly determined by the change in refractive index in a two-dimensional-like optical hotspot near the nanogap. A further step could be taken to increase sensitivity by tuning nanogap-loops to the absorption frequencies associated with the intermolecular vibrational modes of the viruses and fingerprinting them as well.
Keywords: Atomic layer; Atomic layer lithography; Detection methods; Nanogaps; Refractive index sensing; Tera Hertz; Terahertz sensing; Terahertz time-domain spectroscopy; Ultrasensitive; Virus detection; atomic layer lithography; nanogap; refractive index sensing; terahertz sensing; terahertz time-domain spectroscopy; virus